Motivasi dan Hubungkaitnya dengan Prestasi Kerja : Kajian di Kalangan Pengawal Trafik Udara di Jabatan Penerbangan Awam Subang Selangor - Rohani, Ali (2004)
Air Traffic Controller is a challenging profession which demands a full commitment and dedication, that will reflects the image of Department of Civil Aviation, Malaysia. Air Traffic Controllers are responsible for the safety of each and individual movement of flights that pass or transiting into Malaysian’s airspace. It is therefore, considered to be most appropriate to have a study on the performance’s level shown and expected among the controllers in this department and whether the performance is related to any extrinsic or intrinsic motivation and the characteristic of the job itself. Questionnaires were given to the controllers based on the sample size as proposed by Uma Sekaran. The results showed that the controllers have very high job performances and commitment towards their jobs. The intrinsic motivation is the most contributing factor and significantly related to nature and characteristic of the job. They have learn to appreciate lives better and becoming a more responsible person. Even though this profession is of a very high risk, for a controller to be able to get controlling done in a manner that is safe, efficient and orderly, is considered as a self-satisfaction and personnel recognition that nothing can be compared of, thus indirectly contributing to a edges and high job performances. Support and good relationship among supervisors and colleagues are considered to be the most important extrinsic factor besides promotion recognition from department. Based on the findings, recommendations and suggestions were put forward to the management to ensure that the performance’s level and the motivation related are always at the satisfaction level.